Biosensor with total internal reflection imaging ellipsometry. (6th February 2007) - Chen, Y-Y.; Wang, Z-H.; Meng, Y-H.; Jin, G.
In order to monitor multiple protein reaction processes simultaneously, a biosensor based on imaging ellipsometry operated in the total internal reflection mode is proposed. It could be realised as an automatic analysis for protein interaction processes with real-time label-free method. Its principle and methodology as well as a demonstration for its applications are presented.